An analysis of an unstiffened cylindrical shell subjected to internal pressure and axial loading - Houghton, D. S.; Johns, D. J. (College of Aeronautics, 1961)
General equations are obtained for the deflections and stresses in long thin unreinforced cylinders, which are subjected to an axial load and internal pressure. By making suitable simplifying assumptions, results are presented which show the variation of the structural weight parameter with the structural axial loading index, for both pressurised and unpressurised shells. An allowance is made for the effects of shell initial eccentricities on the buckling stress coefficient K, in accordance with R. Ae.S. data sheet 04.01.01. Extreme cases are considered, in which the shell is assumed to be either fully effective (K = 0.6). 0:. completely ineffective (K = 0), in resisting axial compressive loads. For this latter case, complete pressure stabilisation of the shell is considered, and it is shown that the weight penalty involved in using this design philosophy, is negligible for a certain range of the structural loading index. A simple modification to the analysis for this case, i.e. K = 0, is made to allow for the effect of an external longitudinal bending moment.